Synthesis and characterization of ionomers and Poly(fullerene)s for promising application in organic electronics - Bittencourt, Jéssyka Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The development of sensors goes through several parameters that must be analyzed systematically, among them: the potential for rapid detection, sensitivity, selectivity, and portability. For this, the processing of materials, which involves a sensory layer, deserves special attention so that the final performance is satisfactory. In addition to processing, the selection and synthesis of new materials as a sensor element is equally important in the development of versatile devices, bringing new possibilities for systems with reliability and durability. In this sense, polymeric materials are versatile, both in terms of synthesis and processing, opening up new possibilities for sensor devices. This work presents the application of polymeric materials, ionomers and a copolymer based on fullerene, as an ammonia gas sensor produced with different processing techniques, namely: Langmuir-Schaefer, Drop-cast and Spin-coating. The copolymer based on fullerene and Poly(ethylene oxide)-PEO was synthesized during the sandwich doctorate period at the Université de Pau et des Pays de l'Adour, France, at the Institute of Analytical Sciences and Physico-Chemistry for Environment and Materials - IPREM . The devices were characterized through the techniques of visible ultraviolet (UV-vis) spectroscopy, atomic force microscopy (AFM), DC electrical measurements and gas testing with monitoring of the electrical current as a function of the time of exposure to the ammonia gas, in which show that it is possible to apply the materials involved as a sensor element.

O desenvolvimento de sensores passa por vários parâmetros que devem ser analisados sistematicamente, entre eles: o potencial de detecção rápida, sensibilidade, seletividade, preparação da amostra, e portabilidade. Para isso, o processamento de materiais, que envolve uma camada sensorial, merece atenção especial para que o desempenho final seja satisfatório. Além do processamento, a aplicação e síntese de novos materiais como elemento sensor é igualmente importante no desenvolvimento de dispositivos versáteis, trazendo novas possibilidades para sistemas com confiabilidade e durabilidade. Nesse sentido, os materiais poliméricos são versáteis, tanto em termos de síntese quanto de processamento, abrindo novas possibilidades para dispositivos sensores. Este trabalho apresenta a aplicação de materiais poliméricos, ionômeros e um copolímero à base de fulereno, como sensor de gás amônia produzido com diferentes técnicas de processamento, a saber: Langmuir- Schaefer, Drop-cast e Spin-coating. O copolímero à base de fulereno e poli(óxido de etileno)-PEO foi sintetizado durante o doutorado sanduíche na Université de Pau et des Pays de l'Adour, França, no Instituto de Ciências Analíticas e Físico-Químicas do Meio Ambiente e dos Materiais - IPREM. Os dispositivos foram caracterizados através das técnicas de espectroscopia no ultravioleta visível (UV-vis), microscopia de força atômica (AFM), medições elétricas DC e testes de gases com monitoramento da corrente elétrica em função do tempo de exposição ao gás amônia, nos quais mostram que é possível aplicar os materiais envolvidos como elemento sensor.
Síntese e caracterização de ionômeros e Poli(fulerenos) para aplicação promissora em eletrônica orgânica
Keywords: Ionomers; Synthesis; Poly(fullerene)s and organic electronics; Ionômeros; Poli(fulerenos) e eletrônica orgânica